ANALISIS PENERIMAAN SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) DALAM MENUNJANG KINERJA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH (BAPPEDA) DAERAH ISTIMEWA YOGYAKARTA - Yustina Anggita Bajo; Muhammad Zuhdan (Journal Publicuho, 2025)
This study aims to analyse the level of acceptance of the Local Government Information System (SIPD) and its contribution to improving the performance of the Regional Planning and Development Agency (BAPPEDA) of Yogyakarta Special Region. Using a descriptive qualitative approach and the theoretical framework of the Technology Acceptance Model (TAM) by Davis (1989), this study explores employee perceptions of the usefulness and ease of use of SIPD, and uses the approach presented by Dwiyanto (2008) in examining the performance of public sector organizations, which includes five main dimensions, namely productivity, service quality, responsiveness, responsibility, and accountability. Data collection techniques were conducted through in-depth interviews, observation, and document analysis. The results showed that although employees have a positive perception of the perceived usefulness of SIPD, there are still obstacles in the perceived ease of use aspect, such as a less intuitive interface, limited training, and system changes that are not followed by technical assistance. SIPD is proven to contribute to improving work efficiency, inter-sectoral coordination, and information transparency, but has not been optimally utilised. This research recommends system improvements based on user needs, continuous training, and strengthening internal socialisation strategies so that SIPD acceptance can support maximum organisational performance.